Combining scientific research into practical methods to increase the effectiveness of maximal power training - Baker, D.
Power is the most desired physical quality for a number of sports because it entails both force (strength) and velocity (speed) aspects. Power is typically defined as the rate at which work is performed (Mass x Distance / Time). For coaches and sports people it is more often described as strength x speed. Because both strength and speed can be improved by many different training variable manipulations, training to improve power output has been described as requiring a multi-faceted approach (Newton and Kraemer, 1994).